PEMBERDAYAAN MASYARAKAT DALAM PENGADAAN BIBIT MELALUI TEKNIK CABUTAN ALAM DI STASIUN RISET KABUPATEN KUNINGAN PROVINSI JAWA BARAT - Adhya, Ilham; Ismail, Agus Yadi; Indra, Dikki; Zakaria, Zein; Karlina, Lina (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
Conservation of biological natural resources is not only the responsibility of the manager of a conservation area but also the responsibility of all elements, including the community around the area. The activities of conserving biological natural resources that are carried out in collaboration will provide maximum results. Communities around the area in particular are the subject of development in an effort to conserve natural resources. The method of implementing community service activities carried out includes training activities and field practice in stages; preparation, implementation and evaluation. Preparatory activities include field observations regarding the need for facilities and infrastructure. Implementation activities are through training and field practice in the technique of making plant seeds with uprooting techniques in nature. Evaluation activities are carried out after the completion of the activity to ensure the sustainability of the activity. The benefits of this activity are expected to increase public knowledge about the role of providing plant seeds in an effort to restore the area of the Research Station of the Faculty of Forestry, Universitas Kuningan in Gunung Ciremai National Park.